Clavulanic Acid Adsorption Studies in Zeolites - Marcus Bruno Soares Forte; Maria Isabel Rodrigues; Francisco Maugeri Filho (Adsorption Science & Technology)
Zeolites are crystalline inorganic solids containing aluminium, silicon and oxygen arranged in a highly regular structure, and they are usually used in separation processes. In this study, zeolites have been shown to act as adsorbents for clavulanic acid. Ion exchange with different compensating cations (Na + , K + , Ca 2+ , Ba 2+ , Mg 2+ , Sr 2+ ) was used to modify the natural zeolite (NZ) and the synthetic faujasite (13X). Kinetic analysis of the adsorption of clavulanic acid indicated that the 13X-Na zeolite was the most appropriate for this purpose. Under equilibrium conditions, the retention by this zeolite was about 17.4% (C*/C 0 = 0.826), with the amount of clavulanic acid adsorbed relative to the amount of zeolite employed (q*) being ca. 0.5 mg/g. The 13X-Na zeolite was characterized in terms of its Si/Al ratio (1.5), density (d z = 2.248 g/cm 3 ), superficial area (S BET = 444.860 m 2 /g), total pore volume (V pore = 0.308 cm 3 /g), micropore volume (V micro = 0.203 cm 3 /g) and particle porosity (ε p = 0.69). Adsorption isotherms at 10, 15 and 20 °C were constructed using 13X-Na zeolite and solutions of pure clavulanic acid; these demonstrated that the lower the temperature, the higher the amount of clavulanic acid adsorbed.